2016
DOI: 10.1016/j.compscitech.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hierarchy structure on electrical properties of gradient-distribution aluminum oxide/polyethylene nanocomposites

Abstract: In the recent decades, the phenomena of space charge accumulation in the high voltage direct current (HVDC) insulation have attracted more and more attention. In this paper, the gradient-distribution multi-layered Al 2 O 3 /low density polyethylene (LDPE) nanocomposites were prepared via layer-by-layer melting blending and hot pressing method. Morphologies and electrical properties of these gradient-distribution structured composites were discussed. Results showed that this unique structure could largely enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This phenomenon is attributed to the thermal motion of the molecular chains. After heating at 65 °C for 24 h, the molecule rearrangement took place toward the more stable conformations, which resulted in increased DC breakdown strength . After the accelerated migration time exceeds 48 h, the dielectric strength of all samples tends to be steady, indicating that PE/PE- g -AA and PE/u-PE- g -AA blends possess stable and reliable long-time electrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is attributed to the thermal motion of the molecular chains. After heating at 65 °C for 24 h, the molecule rearrangement took place toward the more stable conformations, which resulted in increased DC breakdown strength . After the accelerated migration time exceeds 48 h, the dielectric strength of all samples tends to be steady, indicating that PE/PE- g -AA and PE/u-PE- g -AA blends possess stable and reliable long-time electrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…For ease of analysis, we assumed that the nanoparticles were spherical. In the absence of an applied electric field, we can calculate the attractive potential V A and the repulsive potential V R under the van der Waals and electric doublelayer forces [15,[19][20][21][22]:…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TiO 2 , used as white opacifier [78] or TiO 2 nanoparticles as reinforcing components [79,80] can be suspected as Ti source. Concerning Al, it has been shown that Al 2 O 3 is used as a functional filler to enhance LDPE's dielectric resistance [81,82].…”
Section: Quantification Of Non-certified Elementsmentioning
confidence: 99%